Using specialist GPs to deliver high quality, timely initial health assessments for children in care: A pragmatic response to capacity pressures in community paediatrics - Hewer, Chris; Edwards, Pauline; Bennett, Imelda (Adoption & fostering, 2025)
Initial Health Assessments (IHAs) are a statutory requirement for children entering care in England, mandated to be completed within 20 working days. However, widespread pressures across both community paediatrics and children’s social care are making this increasingly difficult to achieve. Compliance with statutory timescales is highly variable, with some areas reporting compliance rates lower than 50%. The growing demand for neurodevelopmental assessments, national workforce shortages and rising numbers of children in care have stretched capacity and led to delays. This article presents a centralised, general practitioner (GP)-led IHA model developed in Gloucestershire that addresses these challenges through structured training, clinical supervision, peer review and close collaboration with paediatric teams. GPs with safeguarding and child health experience deliver timely, high-quality assessments supported by dedicated administrative systems and robust clinical governance. The model not only improves statutory compliance and relieves pressure on paediatric services, but also ensures consistent, person-centred care for vulnerable children. With its strong results and adaptability, this model offers a scalable and pragmatic solution to the national IHA delivery crisis.